Ionizing Radiation Effect and DNA damage in the workers of Al-Tuwaitha Nuclear Site - Al-Jameel, Lina S.; Ahmed, Rasha S.; Shamran, Haidar A. (Iraqi Journal of Science, 2019)
Single cell gel electrophoresis (SCGE), also called comet assay, is a rapid and sensitive technique used to analyse DNA Fragmentation Index(DFI). This study aimed to evaluate DNA damage in lymphocytes due to ionizing radiation in workers of Al-Tuwaitha nuclear site, which has been used for nuclear activities and contains a potentially significant amount of radioactive waste.The workers in this site are vulnerable to pollution due to a highly polluted environment of ionizing radiation. Blood samples were collected from 36 workerswho were divided into two groups;8 workers without protection and 28workers with protection, in addition to 30 control subjects.Alkaline comet assay was applied for analysis and the results indicated significantly higher DNA damage in the workers without protection as compared with the workers with protection and control groups.The result also showed significant differences between the workers with protection and control groups.